2021
DOI: 10.3390/reports5010001
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status in a Rural Italian Population

Abstract: Vitamin D is known as an antirachitic factor, although it also plays a critical role in several nonskeletal diseases. In our study, we evaluated vitamin D status and sex, age and seasonal association in a general population cohort living in central Italy. Data from 1174 men and 2274 women aged 20–81 were analyzed, and stored serum samples were assayed for 25-hydroxyvitamin D (25(OH)D). Vitamin D was low in both sexes with values significantly lower in women than in men; furthermore, its deficiency was highly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Our third and fourth investigations were conducted in Italy, another country with a warm, Mediterranean environment that experiences an abundance of sunlight. According to a 2021 study by Morsilli et al, young women only acquire adequate vitamin D levels near the end of the summer, and hypovitaminosis D is a common problem in women, even in rural locations with more solar exposure [53]. In their research, 22% of women had insufficient serum levels, and 68.6% were vitamin D deficient.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our third and fourth investigations were conducted in Italy, another country with a warm, Mediterranean environment that experiences an abundance of sunlight. According to a 2021 study by Morsilli et al, young women only acquire adequate vitamin D levels near the end of the summer, and hypovitaminosis D is a common problem in women, even in rural locations with more solar exposure [53]. In their research, 22% of women had insufficient serum levels, and 68.6% were vitamin D deficient.…”
Section: Discussionmentioning
confidence: 96%
“…In their research, 22% of women had insufficient serum levels, and 68.6% were vitamin D deficient. The examination was carried out using a chemiluminescent microparticle immunoassay, and the mean blood concentrations of 25(OH) vitamin D in women were 17.2 ± 10.0 ng/mL [53]. To eliminate seasonal fluctuation, the women who had been recruited in the Anastasi et al study were invited back in July to collect serum for 25(OH) vitamin D measurements [24].…”
Section: Discussionmentioning
confidence: 99%
“…Studies recently conducted in Southern and Western Europe suggest that the prevalence of vitamin D < 50 nmol/L largely varies among countries [ 29 , 30 , 31 , 32 ]. A study conducted in rural areas of Italy found that approximately half of the 3448 included subjects showed vitamin D levels < 50 nmol/L [ 30 ]. A study including ~7000 German adults found that 60% of participants had vitamin D levels < 50 nmol/L [ 31 ].…”
Section: Discussionmentioning
confidence: 99%